Effect of Lubricant Additives on the Oxidation Characteristics of Diesel Engine Particulate Matter - Guangju Xu; Yang Zhao; Mingdi Li; Yanbin Hu; Ling Lin (International Journal of Chemical Engineering)
Three common lubricant additives, including an antioxidant, detergent, and an antifoamer, were added to diesel fuel to perform a diesel engine bench test. Particulate matter samples underwent thermogravimetric analysis to investigate the effect of lubricant additives on the particulate matter oxidation process, characteristic temperature, and activation energy. The results showed the following. Different lubricant additives result in different variation trends in the thermogravimetric curve of a particulate matter sample by varying the rotating speed and torque. When the rotating speed was stable, as the torque increased, the ignition temperature of the particulate matter of Fuel C declined rapidly during the initial stage and then increased rapidly. When the torque was stable, as the rotating speed increased, the ignition temperature of the particulate matter of Fuel C increased initially and then declined. The particulate matter of Fuel C had the lowest level of activation energy at approximately 57.89 J·mol−1. The particulate matter of Fuel A had the highest level of activation energy at approximately 74.10 J·mol−1. When the fuel has a higher cetane number, the combustion chemical reaction rate is faster and results in a more complete reaction. The active substance contact surface increases, which facilitates particulate matter oxidation.